Psychosynthesis : a psychology of the spirit - Firman, John, 1945-2008 (SUNY series in transpersonal and humanistic psychology., 2002)
"Conceived by Italian psychiatrist Roberto Assagioli, psychosynthesis is one of the first Western psychologies that addresses both spiritual development and psychological healing and growth by recognizing and supporting the particular life journey of the person - the individual's own unique path of Self-realization. Firman and Gila present a comprehensive account of psychosynthesis, providing a transpersonal integration of developmental, personality, and clinical theory. They reveal some of the relationships between psychosynthesis and contemporary developmental research, object relations theory, intersubjective psychology, trauma theory, the recovery movement, Jungian psychology, humanistic and transpersonal psychology, and common psychological diagnoses. Case examples and practical theory designed to support both the layperson and the professional seeking to understand and facilitate psychospiritual growth are included."--Jacket